A High Power Driver IC for Electroluminescent Panel: Design Challenges and Advantages of using the Emerging LEES-SMART GaN-on-CMOS process. (2016) - Jia, Zhou; Ge, Tong; Guo, Linfei; Eileen, Ng Pei Jian; He, Huiqiao; Chang, Joseph
Abstract: The Electroluminescent (EL) panel is an emerging backplane lighting technology and becoming increasingly popular in advertising display and facade decoration. Despite the increased popularity of the EL panel, driver circuit for large EL panel is nascent in part because of the required high output power. In this paper, a novel high power EL driver IC based on the emerging LEES-SMART GaN-on-CMOS process are presented and we show that this integrated class-D EL driver is advantageous compared to EL driver IC based on state-of-the-art silicon IC process.